Cu(OTf)(2) or Et3N-catalyzed three-component condensation of aldehydes, amines and cyanides: a high yielding synthesis of alpha-aminonitriles - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Tetrahedron Letters, 2006)
Copper(II) triflate or Et3N have been found to catalyze, under ambient conditions, the addition of a cyanide anion, such as trimethylsilyl cyanide or acetone cyanohydrin, onto in situ generated imines, furnishing alpha-aminonitriles in excellent yields. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; aminonitriles; multicomponent reactions; organocatalyst; Strecker reaction

Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone, novel cytokine modulators via sharpless asymmetric epoxidation and L-proline catalyzed mannich reaction - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Tetrahedron, 2006)
A short and efficient enantioselective synthesis of (-)-cytoxazone and its stereoisomer (+)-epi-cytoxazone, novel cytokine modulators, has been described with good yield and enantioselectivity. Ti-catalyzed Sharpless asymmetric epoxidation of allyl alcohol and L-proline catalyzed three-component Mannich reaction constitute the key steps in introducing stereogenicity into the molecule. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: aminohydroxylation; Asymmetric synthesis; epoxidation; Mannich reaction; Oxidation; Ozonolysis

Cu(OTf)(2) catalyzed high yield synthesis of hantzsch 1,4-dihydropyridines - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2007)
Copper(II) triflate catalyzes efficiently the three-component condensation of aldehydes, beta-ketoesters and ammonium acetate in acetonitrile at 25 degrees C to afford the corresponding Hantzsch 1,4-dihydropyridines in high yields.
Keywords: 4-dihydropyridines; anti-hypertensive drug; calcium channel blockers; cardiovascular diseases; Hantzsch 1; three-component condensation

Cu(OTf)(2) catalyzed Biginelli type condensation of aldehydes, beta-keto esters and carbamates: synthesis of 3,4-dihydro[1,3]oxazin-2-ones - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2008)
Cu(OTf)(2) catalyzes effectively a new multicomponent reaction comprising aldehydes, beta-ketoester and methy carbamate in acetonitrile to afford substituted 3,4-dihydro[1,3]oxazin-2-ones in 60-82% yields. These compounds have been found to show inhibition activity against HL-60 cancer cell.
Keywords: aldehydes; Catalysts; Copper; Multicomponent reaction

Cobalt(II) chloride hexahydrate-diisopropylamine catalyzed mild and chemoselective reduction of carboxylic esters with sodium borohydride - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Synthesis-Stuttgart, 2009)
The cobalt-catalyzed reduction of unsaturated alpha-cyano carboxylic esters using sodium borohydride (NaBH(4)) leads to the corresponding saturated cyano alcohols in high yields. In particular, the new catalytic system cobalt(II) chloride-diisopropylamine in combination with NaBH(4) showed excellent activity in the chemoselective reduction of a variety of carboxylic esters to their corresponding alcohols in good to excellent yields under mild conditions.
Keywords: Alcohols; amines; catalysis; Esters; reductions

Harnessing structure-activity relationship to engineer a cisplatin nanoparticle for enhanced antitumor efficacy - Paraskar, Abhimanyu S.; Soni, Shivani; Chin, Kenneth T.; Chaudhuri, Padmaparna; Muto, Katherine W.; Berkowitz, Julia; Handlogten, Michael W.; Alves, Nathan J.; Bilgicer, Basar; Dinulescu, Daniela M.; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Cisplatin is a first line chemotherapy for most types of cancer. However, its use is dose-limited due to severe nephrotoxicity. Here we report the rational engineering of a novel nanoplatinate inspired by the mechanisms underlying cisplatin bioactivation. We engineered a novel polymer, glucosamine-functionalized polyisobutylene-maleic acid, where platinum (Pt) can be complexed to the monomeric units using a monocarboxylato and an O –> Pt coordinate bond. We show that at a unique platinum to polymer ratio, this complex self-assembles into a nanoparticle, which releases cisplatin in a pH-dependent manner. The nanoparticles are rapidly internalized into the endolysosomal compartment of cancer cells, and exhibit an IC50 (4.25 + 0.16 mu M) comparable to that of free cisplatin (3.87 +/- 0.37 mu M), and superior to carboplatin (14.75 +/- 0.38 mu M). The nanoparticles exhibited significantly improved antitumor efficacy in terms of tumor growth delay in breast and lung cancers and tumor regression in a K-ras(LSL/+)/Pten(fl/fl) ovarian cancer model. Furthermore, the nanoparticle treatment resulted in reduced systemic and nephrotoxicity, validated by decreased biodistribution of platinum to the kidney as quantified using inductively coupled plasma spectroscopy. Given the universal need for a better platinate, we anticipate this coupling of nanotechnology and structure-activity relationship to rationally reengineer cisplatin could have a major impact globally in the clinical treatment of cancer.
Keywords: cancer; chemotherapy; nanomedicine

Cholesterol-tethered platinum II-based supramolecular nanoparticle increases antitumor efficacy and reduces nephrotoxicity - Sengupta, Poulomi; Basu, Sudipta; Soni, Shivani; Pandey, Ambarish; Roy, Bhaskar; Oh, Michael S.; Chin, Kenneth T.; Paraskar, Abhimanyu S.; Sarangi, Sasmit; Connor, Yamicia; Sabbisetti, Venkata S.; Kopparam, Jawahar; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Nanoscale drug delivery vehicles have been harnessed extensively as carriers for cancer chemotherapeutics. However, traditional pharmaceutical approaches for nanoformulation have been a challenge with molecules that exhibit incompatible physicochemical properties, such as platinum-based chemotherapeutics. Here we propose a paradigm based on rational design of active molecules that facilitate supramolecular assembly in the nanoscale dimension. Using cisplatin as a template, we describe the synthesis of a unique platinum (II) tethered to a cholesterol backbone via a unique monocarboxylato and O -> Pt coordination environment that facilitates nanoparticle assembly with a fixed ratio of phosphatidylcholine and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine- N-[amino (polyethylene glycol)-2000]. The nanoparticles formed exhibit lower IC50 values compared with carboplatin or cisplatin in vitro, and are active in cisplatin-resistant conditions. Additionally, the nanoparticles exhibit significantly enhanced in vivo antitumor efficacy in murine 4T1 breast cancer and in K-Ras(LSL/+/)Pten(fl/fl) ovarian cancer models with decreased systemic- and nephro-toxicity. Our results indicate that integrating rational drug design and supramolecular nanochemistry can emerge as a powerful strategy for drug development. Furthermore, given that platinum-based chemotherapeutics form the frontline therapy for a broad range of cancers, the increased efficacy and toxicity profile indicate the constructed nanostructure could translate into a nextgeneration platinum-based agent in the clinics.
Keywords: chemotherapy; nanomedicine